The Relevance of Zakāh Distribution at Indonesia’s National Zakāh Agency (BAZNAS) Pamekasan: The Perspective of ʿUmar ibn al-Khaṭṭāb: Relevansi Pendistribusian Zakat di Badan Amil Zakat Nasional (BAZNAS) Pamekasan: Perspektif ʿUmar ibn al-Khattab - Nurul Fitriyah; Rudy Haryanto; Zainal Abidin (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2023)
This study aims to determine the distribution of zakāh in the Baznas of Pamekasan and the relevance of its zakāh distribution from ʿUmar ibn al-Khaṭṭāb's perspective. This study uses a qualitative research approach and includes qualitative explanatory research with a field research type. The research location is the Baznas of Pamekasan. Data were collected using non-participant observation methods, semi-structured interviews and document study. The study results show that the zakāh distribution pattern at the Baznas of Pamekasan from a regulatory aspect follows Law Number 23 of 2011 concerning zakāh in Indonesia, while the zakāh distribution policy pattern at the Baznas of Pamekasan has relevance to ʿUmar ibn al-Khaṭṭāb's zakāh policy.